RANCANG BANGUN MESIN POTONG PLASTIK ROL BERBASIS MIKROKONTROLLER AT Mega 16 - Setyadjit, Kukuh; Hariadi, Balok (Lembaga Penelitian Dan Pengabdian Kepada Masyarakat Universitas 17 Agustus 1945 Surabaya, 2016)
The developer of the system microcontroller ATMega16 in a control system that is moving forward, facilitate human to do control of such a device automatically without a computer device. This makes the system control in the industry is getting easier and cheaper. In this study will be made in the control system machine pieces of plastic roll on the sensor optocoupler. The equipment uses two motors, dc, of the country to curl up plastic so they form a roll, and the motor still to move heating and cutter. For the process of heating used a wire niklin as for the process of cutting the use of blade saw. To determine the length of plastic pieces then used a sensor optocoupler, and microcontroller ATMega16 as a control centre.Key word: Microkontroler ATMega16, optocoupler.